Migratory Characteristics and Passage of Paddlefishat Two Southeastern U.S. Lock‐and‐Dam Systems. Issue 3 (8th April 2015) - Simcox, Brandon L.; DeVries, Dennis R.; Wright, Russell A.
Abstract: Dams have many effects on river systems, including impeding the migratory movements of fishes. However, locks associated with lock‐and‐dam structures may be useful for passing fish during their migrations. We investigated the potential to facilitate fish passage at dams through two navigational lock structures on the Alabama River, Alabama—Millers Ferry Lock and Dam (L&D) and Claiborne L&D—using targeted, nonnavigational lock operations. The movements of Paddlefish Polyodon spathula with implanted ultrasonic tags and/or radio tags were tracked via both manual receivers and submersible ultrasonic receivers (SURs) deployed inside of the lock chambers and above and below each dam to quantify migration characteristics and determine whether fish passage occurred. We tagged a total of 96 fish (79 received sonic tags, 4 received radio tags, and 13 received both types of tag), and we recorded over 275, 000 SUR detections of 84 individuals and 91 manual detections of 39 individuals. Although nonnavigational lock operations increased the number of days available for potential passage by 0.5–4.7 times, only seven Paddlefish passed upstream through the locks (8% passage rate). Most of the fish movement past dams occurred during spring, when many riverine fish make spawning migrations. Movement past Claiborne Dam occurred most often over the spillway (87% of passage) during high‐water events. Our results suggest that while specialized nonnavigational lock operations along the Alabama River increased opportunities for upstream fish passage, relatively few Paddlefish actually moved upstream through the lock chambers.